Behavioral Relationship Life Clean And Healthy On Knowledge Of Hygiene Personal Students Of State Elementary School Of Gowa District, South Sulawesi - Mustarin, Yanti; Pannyiwi, Rahmat; Latif, Sarifudin Andi; Samila, Samila; Sallo, Andi Kamal M. (International Journal of Health Sciences, 2025)
In Law Number 36 of 2009 Article 79 concerning health, it is emphasized that "School Health" is held to improve the ability of healthy living of students in a healthy environment so that students can learn, grow, and develop harmoniously and as high as possible so that they are expected to become quality human resources. The purpose of the study is to determine whether there is a relationship between knowledge about clean and healthy living and students' personal hygiene. The research method used is analytical study research, stratified random sampling method, the research population is all students of State Elementary Schools in Gowa Regency, South Sulawesi, while the sample to be taken is 44 respondents. The results of the study from 44 respondents, the independent variable is knowledge and the dependent variable is student hygiene, data obtained from respondents using a questionnaire, chi-square statistical test with a level of confidence p = α (0.05) namely knowledge about clean and healthy living behavior (P = 0.00). The conclusion of the study is that there is a relationship between knowledge about clean living and personal hygiene of elementary school students.